1885
DOI: 10.1055/s-0028-1142264
|View full text |Cite
|
Sign up to set email alerts
|

Zum mikroskopischen Nachweis von Cholerabacillen in Dejectionen

Abstract: Mit Berücksichtigung des deutschen Medicinalwesens nach amtlichen Mittheilungen, der öffentlichen Gesundheitspflege und der Interessen des ärztlichen Standes. I. Zum mikroskopischen Nachweis von Cholerabacillen in Dejectionen. Von Professor 11Iax Sehottelius in Freiburg i. B. In Rücksicht auf das allgemeine Interesse , welches gerade jetzt alle die Cholera betreffenden Einzelheiten haben, scheint es angezeigt, kurzen Bericht zu erstatten iiher einige Beobachtungen, welche ich lin vorigen Herbst anzustellen Gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1903
1903
1973
1973

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Schottelius (Schottelius, 1885) was the first to point out the necessity for growing this organism in an alkaline medium, and Loeffier (Loeffier, 1893) found that its isolation from water could be successfully accomplished by_adding 10 c.c.…”
Section: Concentration By Agglutination or Precipitationmentioning
confidence: 99%
“…Schottelius (Schottelius, 1885) was the first to point out the necessity for growing this organism in an alkaline medium, and Loeffier (Loeffier, 1893) found that its isolation from water could be successfully accomplished by_adding 10 c.c.…”
Section: Concentration By Agglutination or Precipitationmentioning
confidence: 99%
“…55 probably be accomplished with somewhat less difficulty than is encountered in the case of B. typhi. Schottelius (Schottelius, 1885) was the first to point out the necessity for growing this organism in an alkaline medium, and…”
Section: Elements Of Water Bacteriologymentioning
confidence: 99%